ORGANIZATIONAL CHANGE DETERMINANTS AND EMPLOYEES BEHAVIOR: A PSYCHOLOGICAL CONTRACT PERSPECTIVE - Muhammad Naseer Akhtar; Lirong Long (European Scientific Journal, ESJ, 2015)
Organizational change as a strategic tool has influenced psychological contracts and fundamentally changed the nature of employment relationships in contemporary organizations. There is a continuous pressure on organizations to adapt new technologies, be competitive in markets, consider strategic outlook, mergers and acquisitions, globalization etc. for their survival. This study is aimed at examining the relationship between determinants of organizational change (impact of change, type of change, frequency of change, successful changes in the past) and intention to quit. In addition, this study offers a comprehensive proposed conceptual model that considers fulfillment of psychological contract (work content, career development, social atmosphere, organizational policies, work life balance, rewards) as mediator with a situational factor like the availability of attractive job alternatives as a moderator.